Gênero e educação: análise de escolhas temáticas de teses e dissertações a partir do conceito de campo - Dutra, Beatriz Campanharo (2021)
This research has as its object of study the thematic choices of students of postgraduate programs in Education (2015-2017). The general objective was to capture elements of the symbolic and subjective field that would allow us to understand how gender, in the intersectionality of race, conditions of origin, and regionality, operates in the thematic choices of theses and dissertations. The specific objectives were intended to investigate expressions of the cultural capital of the graduates and analyse to what extent the social markers of difference contribute to the structuring of the educational field. As hypotheses, it was considered that: a) just as research on the sexual division of labour points to determinants that direct areas of activity according to sex, it was assumed that these factors would explain the tendencies of thematic choices between men and women in the field of Education and b) the social place they occupy in the structure, such as racial belonging, social origin, and regionality, would be decisive markers to their scientific production. Nine universities located in the five Brazilian regions were selected, with an evaluation equal to or higher than 5 to the 2017 quadrennial evaluation by Capes. Data collection was carried through an electronic questionnaire sent via e-mail to the graduates of the programs; the valid responses (129) were processed with the Sphinx iQ2 software. The concepts of sociologist Pierre Bourdieu were adopted as a theoretical reference, based on the concepts of field, habitus and cultural capital. The results indicate that Teacher Training and Educational Policies were the most studied themes, and the reasons for choosing the most recurrent themes were work and graduate studies. In the analysis of the data, there was a special emphasis on the understanding of the object of study from the variations resulting from the socioeconomic conditions of the graduates of the courses, expressed by the mothers' schooling. Regarding the hypotheses, the first one (a) was confirmed, because women are still the main ones responsible for reproductive work. Hypothesis (b) is partially confirmed, since regionality is a conditioning factor in the production of the thematic choice, but not a determining factor. For black and brown women, their racial belonging, their gender, and their social class determine their thematic choices, becoming a means of access and a guarantee of dispute for their permanence in the educational field. In conclusion, gender inequalities are not only expressed explicitly in thematic choices, but are interspersed with the possibilities of choices in the professional field, as well as in the access and permanence in graduate studies and its consequences, such as sandwich scholarships, and that race represents a considerably more expressive marker for non-white people, especially for black women